Current Paradigm of Hepatitis E Virus Among Pediatric and Adult Patients - Belei, Oana; Ancusa, Oana; Mara, Adelina; Olariu, Laura; Amaricai, Elena; Folescu, Roxana; Zamfir, Carmen Lacramioara; Gurgus, Daniela; Motoc, Andrei G.; Stânga, Livia Claudia; Strat, Liliana; Marginean, Otilia (Frontiers in Pediatrics, 2021)
Hepatitis E virus (HEV) infection is a polymorphic condition, worldwide spread among children and adult patients. Multiple studies over the last decade have contributed to a better understanding of the natural evolution of this infection in various population groups, several reservoirs and transmission routes being identified. To date, acute or chronic HEV-induced hepatitis has in some cases remained underdiagnosed due to the lower accuracy of serological tests and due to the evolutionary possibility with extrahepatic manifestations. Implementation of diagnostic tests based on nucleic acid analysis has increased the detection rate of this disease. The epidemiological and clinical features of HEV hepatitis differ depending on the geographical areas studied. HEV infection is usually a self-limiting condition in immunocompetent patients, but in certain categories of vulnerable patients it can induce a sudden evolution towards acute liver failure (pregnant women) or chronicity (immunosuppressed patients, post-transplant, hematological or malignant diseases). In acute HEV infections in most cases supportive treatment is sufficient. In patients who develop chronic hepatitis with HEV, dose reduction of immunosuppressive medication should be the first therapeutic step, especially in transplant patients. In case of unfavorable response, the initiation of antiviral therapy is recommended. In this review, the authors summarized the essential published data related to the epidemiological, clinical, paraclinical and therapeutic aspects of HEV infection in adult and pediatric patients.